MANAGEMENT FISIOTERAPI DENGAN AIRWAY CLEARANCE THECHNIQUES (ACT) PADA KASUS BRONCHIECTASIS DI RUMAH SAKIT PARU BANTUL: A CASE REPORT - Nada Salsabila; Wahyu Tri Sudaryanto; Prayitno Prayitno (Bajang Institute, 2023)
Background: Bronchiectasis is a chronic respiratory disease characterised by widening and thickening of the airways, leading to accumulation of secretions and recurrent infections. Airway clearance techniques (ACT) are non-pharmacological strategies to improve symptoms, health-related quality of life and reduce exacerbation frequency. Objective: knowing physiotherapy management with airway clearance techniques in case bronchiectasis. Methods: research using case report method at RS Paru Respira Bantul in a 63 years old female patient with diagnosed bronchiectasis with complaints of coughing and sputum that are difficult to get out. Patients were given intervention once a week for two weeks. Result: the intervention was carried out two times resulted in BORG scale was decrease, peakflow was decrease, voldine increase, measurement of the thoracic cage in the axilla has increased, and for the patient's functional abilities did not change from the first to the last intervention. Conclusion: Based on the research using Case Report, it shows that physiotherapy management with ACT method in cases of bronchiectasis, as a whole the evaluation results found an increase.